2023
DOI: 10.1007/s40615-023-01668-5
|View full text |Cite
|
Sign up to set email alerts
|

High Systolic Blood Pressure of High-Income African American Children

Abstract: Background According to the Minorities’ Diminished Returns (MDRs) theory, racism may reduce the health returns of family socioeconomic status (SEP) resources such as family income for racial minorities, particularly African Americans, compared to Whites. However, we are unaware of any previous studies on racial variation in the protective effects of family income on children’s blood pressure. Aim We conducted this study to compare the overall effects of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
0
0
Order By: Relevance
“…According to Marginalization-related Diminished Returns (MDRs) theory 15,16 , the educational gradient in health is weaker for marginalized populations. Research has shown that almost all types of social marginalization (e.g., based on race, ethnicity, sexual orientation, and immigration) reduce the strength of the protective effect of educational attainment on health outcomes [17][18][19][20] . A few studies have also shown that immigration may also be associated with weaker health effects of educational attainment 14,[21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…According to Marginalization-related Diminished Returns (MDRs) theory 15,16 , the educational gradient in health is weaker for marginalized populations. Research has shown that almost all types of social marginalization (e.g., based on race, ethnicity, sexual orientation, and immigration) reduce the strength of the protective effect of educational attainment on health outcomes [17][18][19][20] . A few studies have also shown that immigration may also be associated with weaker health effects of educational attainment 14,[21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%